Factors Associated With The Occurrence of Contact Ddermatitis in The Working Area Of Telaga Dewa Health Center, Bengkulu City - Dannia, Ela Rahma; Habibi, Julius; Suyanto, Jipri; Fauzi, Yusran; Wulandari, Wulandari (Journal Hygeia Public Health, 2024)
Intoduction: Contact dermatitis is a skin disease caused by irritants or contact with allergens. According to data from the World Health Organization (WHO), there was an increase of about 7% in 2022 from the general population, including 3-24% in children and 33-64% in the elderly. It ranks among the top 10 diseases reported to the Health Office of Bengkulu Province and City, with an increase of 1555 cases at Telaga Dewa Health Center in 2023. This study aims to identify the factors related to the incidence of dermatitis at Telaga Dewa Health Center in Bengkulu City in 2024.Method: This research is quantitative with a cross-sectional design. The sample consists of 69 individuals, selected through simple random sampling. The tests used include univariate and bivariate tests, and data analysis was conducted using the chi-square test. Result and Discussion: he analysis results show that nearly half (47.8%) of the respondents have inadequate knowledge, the majority of respondents (72.5%) are employed, a large portion of respondents (53.6%) have poor personal hygiene, and most respondents (59.4%) are suffering from contact dermatitis at Telaga Dewa Health Center in Bengkulu City. There is a relationship between knowledge and the incidence of contact dermatitis with a p-value of 0.003, employment with a p-value of 0.000, and personal hygiene with a p-value of 0.000. Conclusion: It is expected that dermatitis sufferers will maintain factors related to the incidence of contact dermatitis and undergo regular check-ups at Telaga Dewa Health Center.